Analisis Dampak Film Ticket to Paradise dalam Penguatan Citra Bali Sebagai Destinasi Wisata Budaya - Antonius Jefrianus F. Bria; Ni Made Gandhi Sanjiwani (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This research was conducted in Bali, specifically focusing on the influence of the film "Ticket to Paradise" in strengthening Bali's image as a cultural tourism destination globally. The purpose of this study was to analyze the film's impact on tourist perceptions and its contribution to strengthening Bali's cultural appeal through visual media. The benefits of this research are twofold: academic benefits in strengthening the literature in the field of tourism and media communication, and practical benefits for tourism stakeholders in optimizing film as a destination promotion tool. The method used in this study was a qualitative approach, with data collection techniques through in-depth interviews with informants from diverse backgrounds. The results indicate that the film "Ticket to Paradise" has a positive impact in five main aspects: increased tourist interest, influence on travel preferences, promotional cost efficiency, enhanced positive image through visuals, and long-term economic opportunities. However, the findings also indicate that this influence is not fully distributed, primarily because the film was not produced directly in Bali, thus suboptimal local economic opportunities. Therefore, this study emphasizes the importance of synergy between the local film and tourism industries in promoting sustainable and authentic cultural destination promotion through media communication.